Retrospective Cohort Study to Examine Disease Progression in Retinitis pigmentosa Patients Seen at the University of Ottawa Eye Institute - Kandakji, Lynn (Université d'Ottawa / University of Ottawa, 2024)
Retinitis pigmentosa (RP) is the most common form of inherited retinal degeneration, heterogenous in its clinical presentation and genetic cause. Understanding the short-term disease mechanisms is pivotal for the development of new therapies. Upcoming clinical trials will take genotype-agnostic approaches; therefore, a comprehensive analysis of progression that encompasses many genetic factors will be needed. In this 10-year retrospective cohort study, rates of progression were measured, structurally and functionally, in 85 RP patients seen at the Ottawa Eye Institute. Parameters examined were the ellipsoid zone (EZ) length on an optical coherence tomography (OCT) image, Humphrey and Goldmann visual fields (VF), and full-field and multifocal electroretinograms (ERGs). RP is revealed to have a 1st order exponential decay pattern of loss, with mean rates of decline of 7.65 %/year for ellipsoid zone (EZ) length, 6.35%/year, 4.39%/year, and 1.57%/year for the Humphrey VF 30-2, 24-2, and 10-2 mean deviation (MD) respectively, and 5.22%/year, 7.77%/year, 6.77%/year, 6.80%/year, and 12.45%/year for Goldmann V4e, III4e, I4e, I3e, and I2e isopter lengths, respectively. In cases where different diagnostic tests were conducted within 3 months of each other, the data was analysed to determine if there was a positive correlation between the diagnostic tests. Ellipsoid zone length and Humphrey 24-2 mean deviation exhibited the strongest association with a coefficient of 0.99. The study reveals structural and functional changes in advanced retinitis pigmentosa and presents a protocol for assessing short-term progression.
Keywords: retinitis pigmentosa; progression; genetics; prediction; inherited retinal degeneration; optical coherence tomography; visual field; electroretinography